SISTEM INFORMASI MONITORING EKSPEDISI PENGIRIMAN BARANG BERBASIS WEBSITE PADA PT. RIDHO MAKMUR SENTOSA - Elsafanni Putri (2023)
PT. Ridho Makmur Sentosa is a company that runs its business in the service sector, namely the delivery of goods. In the business process there are obstacles such as customers who have not been able to track the position of their goods sometimes contact administrative staff to find out the position of the goods which can hinder performance and waste time. Therefore, in this study, researchers designed a web-based online information system that is expected to help customers find information or those who want to send goods using this company's expedition services, and also customers can observe directly the position of the goods being sent. In this study, the waterfall method was used in designing information systems and black box testing in system testing. Based on this research, an information system is produced that contains information related to tracking goods shipments, company profiles, customer data, goods delivery data, changes in goods tracking status, and reports that can help customers get the information they need more quickly and easily.